2010
DOI: 10.1002/ar.21312
|View full text |Cite
|
Sign up to set email alerts
|

Locations of the Motor Endplate Band and Motoneurons Innervating the Sternomastoid Muscle in the Rat

Abstract: Sternocleidomastoid (SCM) is a long muscle with two bellies, sternomastoid (SM) and cleidomastoid (CM) in the lateral side of the neck. It has been widely used as muscle and myocutaneous flap for reconstruction of oral cavity and facial defects and as a candidate for reinnervation studies. Therefore, exact neuroanatomy of the SCM is critical for guiding reinnervation procedures. In this study, SM in rats were investigated to document banding pattern of motor endplates (MEPs) using whole-mount acetylcholinester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…As reported, the SM motoneurons were typically located in the lower MO and spinal ventral grey horn in the C1-C2. 59 For example, the SM motoneurons in C1 were concentrated predominantly in the dorsomedial (DM) region, whereas the SH motoneurons at this level were located mainly in the VM region of the ventral horn (Figure 9C). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, the SM motoneurons were typically located in the lower MO and spinal ventral grey horn in the C1-C2. 59 For example, the SM motoneurons in C1 were concentrated predominantly in the dorsomedial (DM) region, whereas the SH motoneurons at this level were located mainly in the VM region of the ventral horn (Figure 9C). …”
Section: Resultsmentioning
confidence: 99%
“…The details regarding HRP labeling have been given in our recent publication. 59 Briefly, 30 % HRP (type VI A, Sigma Chemical, St. Louis, MO) solution was injected at two points (5μL/point) into the MEP band in the right NMEG reinnervated SM muscle and the left SH muscle (control) with Hamilton microsyringe. After a survival time of 48 hours, the animals were deeply anesthetized with sodium pentobarbital (60 mg/kg i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…The present study showed that NMEG produced a better recovery of muscle force and larger muscle weight as compared with conventional EEA nerve repair. Retrograde horseradish peroxidase (HRP) tracing [46] confirmed that the XI nerve-innervated SM muscles were reinnervated by motoneurons from the SH nerve pool in C1-C2 in the NMEG group. The mean weight of the NMEG reinnervated muscle (with immediate reinnervation after denervation) measured at 3 months after reinnervation was 87% of the control (intact SM on the opposite site).…”
Section: Discussionmentioning
confidence: 99%
“…We recently developed a new reinnervation technique called “nerve-muscle-endplate band grafting (NMEG)” [28] and conducted a series of experiments in a rat model [2933]. The development of this technique is based on the concept that a healthy motor endplate band with a nerve branch and terminals that innervates an expendable muscle can be transplanted to a more functionally important denervated muscle for restoring its motor function.…”
Section: Introductionmentioning
confidence: 99%